Plan de promoción y publicidad para la confitería el Pauteñito, de la ciudad de Quevedo - Jiménez Soria, Miryan Elizabeth (2012)
The present investigation had as objective to create the promotion plan and publicity for the sweet shop The Pauteñito the same one that settled down in Quevedo from the year of 1963, from its beginnings it was a store in which could be products of first necessity, national and foreign liquors, candies, cigarettes, machetes, bullets ..etc…, starting from the year 2008, the Pauteñito intruded in a new market, that of the party articles, having a great selection of articles and products at the present time to carry out all type of social acts, already maintaining its Fair of the Candy traditional. You could determine that the promotion that more she/he gets the attention to the interviewed clients they are the discounts, a great percentage of potential clients if they know the sweet shop The Pauteñito, but they ignore that she/he sells articles of parties. Of the interviewed clients 56% has not listened publicity of the sweet shop in any means of communication, while 44% yes, what takes to conclude that most of the clients visit The Sweet shop more for tradition than for the publicity in massive means. is proven the hypothesis settled down in the investigation The lack of a promotion plan and publicity that she/he informs the new commercial acting it impacts negatively in the level of sales that has the sweet shop The Pauteñito in the market of Quevedo. Inside the proposal you design the logo of the company and slogan that will serve so that the clients and potential client also recognize the service that lends this company, the promotion plan and publicity with which the company waits to increase their clients.